Penguatan Budaya Literasi Digital Islami Melalui Edukasi Pemanfaatan Media Sosial di Kelurahan Cilaku - Yuniar, Euis Ismayati; Jalaludin, Ega; Aeni, Gita Kurotul; Hesti, Neng; Pratama, Yofie (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
The lack of Islamic digital literacy not only increases the risk of spreading hoaxes and violating communication ethics but also results in a lack of understanding of how to utilize digital media for social and economic needs. The objective of this community service focuses on strengthening the culture of Islamic digital literacy and improving the quality of social media utilization for the advancement of Cilaku Village residents, using the Asset-Based Community Development (ABCD) approach, namely the stages of